There Is No Association Between the Number of Stent Retriever Passes and the Incidence of Hemorrhagic Transformation for Patients Undergoing Mechanical Thrombectomy - Hassan, Ameer E.; Kotta, Hari; Shariff, Umar; Preston, Laurie; Tekle, Wondwossen; Qureshi, Adnan (Frontiers in Neurology, 2019)
Background: Previous research has focused on the association between hemorrhagic transformation (HT) incidence and pre-procedural variables (i.e., baseline variables) rather than the association between HT incidence and endovascular treatment (EVT) procedural variables (e.g., stent retriever passes). Objective: To assess the association, if any, that exists between the number of stent retriever passes per procedure and the incidence of HT for patients undergoing mechanical thrombectomy. Methods: An endovascular database from a comprehensive stroke center was used to collect data on EVT patients treated with Trevo, Solitaire, or Penumbra stent retrievers from the years 2012 to 2017. Statistical analyses were conducted on the stent retriever passes, demographics, morbidities, medication usage, and outcomes and their association with HT. Results: Of the 329 total patients, 46 (14%) had HT. The HT group had an average [SD] of 1.65 [0.67] and range of [1–3] passes per procedure while the non-HT group had an average [SD] of 1.63 [0.86] and range of [1–5] passes per procedure. Admission NIHSS score (p = 0.0003) and the incidence of diabetes mellitus (DM) (p = 0.05) were significantly higher in the HT group. Subdividing HT into symptomatic and asymptomatic ICH groups failed to display significant differences in the distribution of the stent retriever passes (p = 0.969). The number of passes failed to show any association with HT (p = 0.804) while admission NIHSS score was found to have an OR of 1.07 (95%CI: 1.029–1.121, p = 0.001) with HT incidence. Conclusion: No significant association was found between HT incidence and the stent retriever passes. Further multicenter studies are warranted to corroborate our results.